2022
DOI: 10.1038/s41598-022-21577-7
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles gambiae s.l. swarms trapping as a complementary tool against residual malaria transmission in eastern Gambia

Abstract: Malaria remains a major health problem and vector control is an essential approach to decrease its burden, although it is threatened by insecticide resistance. New approaches for vector control are needed. The females of Anopheles gambiae s.l. mate once in their life and in the swarms formed by males. Trapping swarms of Anopheles gambiae s.l. males is a potential new intervention for vector control, alternative to the use of insecticides, as it would disrupt mating . The proof-of-concept pilot study aiming at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(46 reference statements)
2
1
0
Order By: Relevance
“…Our results showed that swarms were always initiated by 1 or 2 males displaying a tortuous flight pattern as found in other studies (Charlwood et al 2002, Diabate et al 2003, 2009, Assogba et al 2014, 2022, Sawadogo et al 2014). During swarming, females approach swarms to select a mating partner then leave the swarm with the selected male in copula (Diabate et al 2003, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results showed that swarms were always initiated by 1 or 2 males displaying a tortuous flight pattern as found in other studies (Charlwood et al 2002, Diabate et al 2003, 2009, Assogba et al 2014, 2022, Sawadogo et al 2014). During swarming, females approach swarms to select a mating partner then leave the swarm with the selected male in copula (Diabate et al 2003, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, studies in Benin have shown the association between indoor resting density and swarm size (Assogba et al 2014). However, the same pattern of small swarming size with low indoor resting density was found in The Gambia (Assogba et al 2022), a bordering country of Senegal and close by this study areas. Therefore, more research is needed to further characterize factors likely influencing the swarm size and the potential contribution of indoor resting density.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings offer compelling evidence that mosquitoes actively process and integrate visual and acoustic information, a discovery that has implications for both ecological research and public health initiatives, particularly in the context of vector control. Notably, previous interventions targeting male mosquito swarms have been linked to reduced female insemination rates and decreased malaria prevalence, highlighting the potential of swarm-based interventions in vector management ( 8 , 78 ). Yet, the practical application of this strategy has been often limited by reliance on insecticides or labor-intensive manual trapping methods.…”
Section: Discussionmentioning
confidence: 99%